Surgical Treatment of Racemose Cysticercosis in the Quadrigeminal Cistern: A Case Series - Guilherme Nobre Nogueira; Rafaela Fernandes Gonçalves; Eberval Gadelha Figueiredo; Gustavo Rassier Isolan (Brazilian Neurosurgery)
Introduction Racemose neurocysticercosis is rare and distinctive among the variety of neurocysticercosis pathologies, and it is characterized by the development of cysts in the basal subarachnoid region. This uncommon presentation involves the formation of multiple, non-encapsulated cystic membranes resembling a bunch of grapes due to the exogenous budding of aberrant proliferating Taenia solium larvae. Typically observed in expansive areas of the brain, such as the suprasellar, sylvian, and quadrigeminal cisterns, or around the rostral brainstem, these cysts lack scolex, do not always involve edema, and can escape detection with contrast enhancement depending on their life cycle.